BLOOD PRESSURE CONTROL WITH BENSON RELAXATION TECHNIQUE IN HYPERTENSIVE PATIENTS - Ramadhani, Dwi Yuniar; Annisa, Dinda Rahma; Suwandi, Putri Nabila Savira; Ulan Apriani; Aini, Diah Qurrotul; Dinata, Anggi Zubatian Artha (Journal of Vocational Nursing, 2023)
Introduction: A person who has high blood pressure sometimes has difficulty controlling blood pressure. As a result of uncontrolled blood pressure will cause various complications. Efforts that may be made to control blood pressure and avoid depression can be done by using non-pharmacological techniques, one of which is by using relaxation techniques. To find out blood pressure before and after Benson's relaxation technique is carried out in patients with hypertension. Methods: The research design used was quasy experimental, where there were 2 groups, namely the treatment group and the control group.  The population of people with hypertension was 38 respondents and simple random sampling technique. Respondents were divided into 2 groups.  Insresearch instruments used observation sheets and Geriatric Depression Scale (GDS). Statistical test used wilcoxone Signed Rank Test. Results: It was found that 19 respondents (100%) were found to have decreased blood pressure levels. In the control group or the group that did not do Benson relaxation technique, there was a decrease in blood pressure in as many as 9 respondents (47%). The Geriatric Depression Scale (GDS) value is known that as many as 34 people with hypertension (89%) fall into the category of mild depression with a score of 10-19, the intervention group is 18 people (95%) and 16 people (84%).  Benson's relaxation technique on blood pressure obtained a value of p = 0.000 which shows that the influence of Benson's relaxation technique with blood pressure in hypertensive patients. Conclusions:Benson's relaxation technique done regularly will help lower blood pressure and provide relaxation to the muscles so as to reduce muscle tension, reduce stress and calm mind.